2005
DOI: 10.1021/bi048216r
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Interactions Involving Lysine Make Major Contributions to Collagen Triple-Helix Stability

Abstract: Important stabilizing features for the collagen triple helix include the presence of Gly as every third residue, a high content of imino acids, and interchain hydrogen bonds. Host-guest peptides have been used previously to characterize triple-helix propensities of individual residues and Gly-X-Y triplets. Here, comparison of the thermal stabilities of host-guest peptides of the form (Gly-Pro-Hyp)3-Gly-X-Y-Gly-X'-Y'-(Gly-Pro-Hyp)3 extends the study to adjacent tripeptide sequences, to encompass the major class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
172
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(178 citation statements)
references
References 47 publications
2
172
0
2
Order By: Relevance
“…The salt bridges observed in our solution structure are able to explain the surprisingly high thermal stability of homotrimeric triple helices with the KG(D/E) sequence (21), as well as our own heterotrimer (16). The inter-chain charge pairs that can be formed in those systems, homotrimers or heterotrimers, are equivalent and occur from the K in triplet n of one chain and interact with the D in triplet n ϩ 1 of the next chain.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…The salt bridges observed in our solution structure are able to explain the surprisingly high thermal stability of homotrimeric triple helices with the KG(D/E) sequence (21), as well as our own heterotrimer (16). The inter-chain charge pairs that can be formed in those systems, homotrimers or heterotrimers, are equivalent and occur from the K in triplet n of one chain and interact with the D in triplet n ϩ 1 of the next chain.…”
Section: Discussionmentioning
confidence: 56%
“…For this reason, their role in the stabilization of the triple helix (38), the supramolecular assembly of collagen (39), and its interactions with other macromolecules (10) has been actively researched in the past few years. Experiments focused on determining the relationship between sequence and thermal stability of the triple helix found that model homotrimeric peptides containing the motif XKGDYЈG or XKGEYЈG are particularly stable (21). Changing the order of the charged amino acids or replacing Lys with Arg results in a decrease in the melting temperature of the assembly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The related peptide GFASPAGPO was synthesized which reverses the location of the low-stability GFA triplet and the high-stability GPO triplet (Table 6). Previous studies suggested that in the absence of a mutation, the interchange of triplets located at different positions does not affect thermal stability unless favorable charge interactions are created (31,32). The CD spectra of both peptides exhibit a maximum at 225 nm, which is characteristic of the triple-helix conformation ( Figure 4A), but peptide GFASPAGPO (3700 deg cm 2 dmol -1 ) exhibited a slightly higher mean residue ellipticity (MRE 225 ) compared to peptide GPOSPAGFA (3570 deg cm 2 dmol -1 ).…”
Section: Predicting Lethality From Position and Amino Acidmentioning
confidence: 99%